European Union Transnational Cooperation in Two Programming Periods: 2007-2013 and 2014-2020 - Marek PRONIEWSKI; Emilia JANKOWSKA-AMBROZIAK (Communications of International Proceedings, 2021)
European transnational cooperation is one of the three levels of cooperation supported by the EU's cohesion policy. It concerns the cooperation of larger regions, which would be difficult or even impossible without additional financial and methodological impulses due to the large areas in which cooperation is undertaken and the distance between potential partners. The authors of the article attempt to indicate the progress in the implementation of transnational cooperation programs in two consecutive programming periods 2007-2013 and 2014-2020. In economic terms, both periods experienced difficult moments, which was reflected in the course of cooperation. We are talking about the economic crisis and its long-term consequences, or the refugee crisis, which had a significant impact on cooperation between countries. Despite these events, cooperation programs have resulted in numerous projects, hundreds of project partners and full use of financial resources.
Keywords: Transnational Cooperation; European Union; Taxonomy.